Safety and Intranasal Retention of a Broad-Spectrum Anti-SARS-CoV-2 Monoclonal Antibody SA55 Nasal Spray in Healthy Volunteers: A Phase I Clinical Trial - Chaoying Hu; Yibo Zhou; Xing Meng; Jianhua Li; Jinxia Chen; Zhifang Ying; Xiaoliang Sunney Xie; Yaling Hu; Yunlong Cao; Ronghua Jin (Pharmaceutics)
Background: A broad-spectrum anti-SARS-CoV-2 monoclonal antibody (mAb), SA55, is highly effective against SARS-CoV-2 variants. This trial aimed at demonstrating the safety, tolerability, local drug retention and neutralizing activity, systemic exposure level, and immunogenicity of the SA55 nasal spray in healthy individuals. Methods: This phase I, dose-escalation clinical trial combined an open-label design with a randomized, controlled, double-blind design. Healthy participants aged 18–65 years were enrolled and received a single dose of the SA55 nasal spray (1 mg or 2 mg) or multiple doses of SA55 nasal spray/placebo for 7 days (1 or 2 mg/dose, 3 or 6 doses/day). Safety monitoring was conducted throughout the study. Nasal swabs and venous blood samples were collected to analyze local drug concentration/neutralization, systemic exposure, and immunogenicity. Results: From 2 June to 11 August 2023, 80 participants were enrolled and received study intervention. The severity of adverse reactions (ADRs) reported during the study was mild in all cases, and all ADRs were laboratory test abnormalities without corresponding symptoms or vital signs. A total of 9 ADRs were reported, of which all were mild in severity. Overall ADR incidence rate was 16.67% (8/48) in single-dose groups and 4.17% (1/24) in multiple-dose groups. The nasal local drug concentration and neutralizing activity were generally stable within 4–8 h, with favorable neutralization activity against Omicron BF.7 and XBB strains. Conclusions: This study demonstrated favorable safety and tolerability of the SA55 nasal spray in healthy volunteers, exhibited satisfactory neutralizing activity against Omicron variants intranasally, and indicated low systemic toxicity risk.